Urkunden und Memorialquellen zur älteren Geschichte des Klosters Rosazzo - Härtel, Reinhard (Verlag der Österreichischen Akademie der Wissenschaften, 2018)
The edition of the documentary sources comprises the list of donations which contains reports from (allegedly) 1060 to 1341, also charters from 1135 to 1249 and supplementary sources especially from the later Middle Ages, however with lots of references to the early days of the history of the monastery. This is followed by the necrology written shortly before 1300 which has unusually close ties to the list of donations, and the calendar. Additionally there are extensive discussions concerning the history of research, the manuscripts, to certain sources up to controversival questions of localization.